Implementation of Restaurant Tax Policy at Anugerah Restaurant Leilem Village Minahasa Regency - Clieverson A. Lolaroh; Marthinus Mandagi; Margareth I.R. Rantung (Technium Social Sciences Journal, 2023)
In this study it shows that taxpayers do not pay taxes, because initially the turnover decreases so they do not pay taxes, for employees who are in charge of collecting taxes are also less assertive in collecting taxes and the taxpayers lack understanding about taxes because taxpayers prefer to open their business rather than participate socialization. For the tax due limit, the Anugerah restaurant has exceeded the limit because the last tax payment for the grace restaurant is in 2021, the restaurant should have been temporarily closed according to the regent regulations Minahasa Regent Regulation Number 6 of 2011 Concerning the System, Procedures and Sanctions for Collection of District Taxes Minahasa, and suggestions for supporting tax collection facilities are not functioning properly. For Enforcement of Sanctions at the Anugerah restaurant, it is not yet firm because it has only arrived at the first warning letter, if you look at Perbup number 6 of 2011 the restaurant has been temporarily closed because it is appropriate terms of temporary suspension of business, from the results of the study it was found that the implementation of restaurant taxes in Anugerah restaurants was not going well because they were no longer paying taxes and the regent’s regulation policies were not going well because employees were not strict in giving sanctions to Anugerah restaurants